2015
DOI: 10.1016/j.celrep.2015.02.057
|View full text |Cite
|
Sign up to set email alerts
|

NFIL3 Orchestrates the Emergence of Common Helper Innate Lymphoid Cell Precursors

Abstract: Innate lymphoid cells (ILCs) are a family of effectors that originate from a common innate lymphoid cell progenitor. However, the transcriptional program that sets the identity of the ILC lineage remains elusive. Here, we show that NFIL3 is a critical regulator of the common helper-like innate lymphoid cell progenitor (CHILP). Cell-intrinsic Nfil3 ablation led to variably impaired development of fetal and adult ILC subsets. Conditional gene targeting demonstrated that NFIL3 exerted its function prior to ILC su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
138
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(143 citation statements)
references
References 50 publications
(87 reference statements)
3
138
2
Order By: Relevance
“…Nevertheless, Nfil3 is not universally required for ILC differentiation as liver-resident ILC1 and those found in the skin, uterus, and salivary gland were also unaffected (Cortez et al 2014;Seillet et al 2014a, b;Sojka et al 2014). Indeed, Nfil3 appears to be only to be important early in ILC development as deletion of Nfil3 in mature cells using NKp46 iCre or Rorγt Cre cells has no effect on lineage maintenance or homeostasis of NK cells, or ILC3, respectively (Firth et al 2013;Xu et al 2015).…”
Section: Nuclear Factor Interleukin-3 (Nfil3)mentioning
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, Nfil3 is not universally required for ILC differentiation as liver-resident ILC1 and those found in the skin, uterus, and salivary gland were also unaffected (Cortez et al 2014;Seillet et al 2014a, b;Sojka et al 2014). Indeed, Nfil3 appears to be only to be important early in ILC development as deletion of Nfil3 in mature cells using NKp46 iCre or Rorγt Cre cells has no effect on lineage maintenance or homeostasis of NK cells, or ILC3, respectively (Firth et al 2013;Xu et al 2015).…”
Section: Nuclear Factor Interleukin-3 (Nfil3)mentioning
confidence: 90%
“…Firstly, in the αLP population, Nfil3 is suggested to be primed to induce ILC commitment through the induction of the transcription factor TOX ). In the second mechanism, Nfil3 is proposed to act on the CHILP to induce Id2 expression (Xu et al 2015). Currently, the relationship between αLP and CHILP is not clear and whether Nfil3 acts at two different stages in ILC progenitors is not yet clear.…”
Section: Nuclear Factor Interleukin-3 (Nfil3)mentioning
confidence: 99%
“…Up-regulation of Zbtb16, Nfil3, Id2, and Il2rb in Bcl11b-deficient cells provides both growth support and identity functions for NK and ILC fates outside of the conventional αβ T-cell pathway (43,53,57,58). Many Bcl11b KO cells also up-regulate the phase 1-specific Notch-negative feedback regulator, Nrarp, which is also highly expressed in NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…The second group consists of genes that are normally not activated to substantial levels at all during the phase 1 stages. Curiously, these are highly enriched for genes used in NK cells, ILCs, and innate-like T cells, including the powerful regulatory genes Id2, Zbtb16, and Nfil3 (6,42,(49)(50)(51)(52)(53)(54)(55). Many of these genes, especially NK-associated genes, require continual Bcl11b action to keep them silent later (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies suggested an Nfil3-independent pathway in specific immature subsets of NK cells (Crotta et al 2014;Seillet et al 2014a), or tissue-resident NK cells such as those found in liver or salivary glands (Cortez et al 2014;Sojka et al 2014). In addition, several groups reported that Nfil3-deficient mice lacked all ILC subsets (Geiger et al 2014;Seillet et al 2014b;Xu et al 2015;Yu et al 2014), suggesting that Nfil3 promotes Tox expression , and providing further evidence that Nfil3 acts on a shared progenitor (some have termed common innate lymphoid progenitor or "CILP") that gives rise to both NK cells and ILCs. Although later studies revealed additional defects in other immune compartments, including T cells, the overwhelming deficiency is in the NK cell and ILC populations.…”
Section: Generation Of An Nk Cell From a Common Lymphoid Progenitormentioning
confidence: 96%